The policy of mover school as a catalyst for improving the quality of education - Meydia Afrina; Jumiati Siska; Okky Leo Agusta; Rambat Nur Sasongko; Muhammad Kristiawan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This article aim to analyze of the policy form of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia in collaboration with local governments, followed by early childhood education programs, Primary School, Junior High School, Senior High School, Extraordinary School both public and private in the Motivating School Program whether or not it can be implemented. This research uses a qualitative approach. The data collection technique used in this study is library research. In this literature study, the author collects materials related to research from books, scientific journals, literatures and other publications that are worthy of being used as sources, by describing and describing the data through several expert opinions. The result of this research is that the Driving School program has an impact as a catalyst for the quality of education in Indonesia. This is indicated by the existence of several interventions. The interventions carried out in the motivating school program start from human resources, learning with a new paradigm and data-based planning. This program is able to accelerate public/private schools to move 1-2 stages further. However, because it is still dynamic, some of the readiness in the curriculum is still not optimal. This program is able to accelerate public/private schools to move 1-2 stages further. However, because it is still dynamic, some of the readiness in the curriculum is still not optimal.